Marrow adipose tissue: trimming the fat - Scheller, Erica L. (Trends Endocrinol Metab, 2016)
Marrow adipose tissue (MAT) is a unique fat depot, located in the skeleton, that has the potential to contribute to both local and systemic metabolic processes. In this review we highlight several recent conceptual developments pertaining to the origin and function of MAT adipocytes; consider the relationship of MAT to beige, brown, and white adipose depots; explore MAT expansion and turnover in humans and rodents; and discuss future directions for MAT research in the context of endocrine function and metabolic disease. MAT has the potential to exert both local and systemic effects on metabolic homeostasis, skeletal remodeling, hematopoiesis, and development of bone metastases. The diversity of these functions highlights the breadth of MAT’s potential impact on health and disease.